Dampak Pembelajaran Kontekstual Terhadap Keterlibatan Siswa Dan Prestasi Akademik Dalam Pendidikan IPS - romdloni, mukhamad (Impressive: Journal of Education, 2024)
This study aims to examine the impact of implementing contextualized learning on students' engagement and their academic achievement in education. This quantitative research used an experiment with a control and experimental group design, with a population of 300 grade X students from MA Mamba'us Sholihin. The experimental group was treated using the contextualized learning model, while the control group followed conventional learning. Data were collected through student engagement surveys, learning outcome tests, and direct observation during the learning process. The results showed that students who learned with the contextual approach showed a higher level of engagement compared to the control group. In addition, they also obtained better academic results in the final exam. The findings suggest that contextualized learning can increase students' motivation and support higher academic achievement in their learning at the boarding school.